2004
DOI: 10.1042/bj20030818
|View full text |Cite
|
Sign up to set email alerts
|

Venom phospholipases A2 of bamboo viper (Trimeresurus stejnegeri): molecular characterization, geographic variations and evidence of multiple ancestries

Abstract: Phospholipases A2 (PLA2s) were purified from the Trimeresurus stejnegeri venom obtained from various localities in Taiwan and three provinces in China, by gel filtration followed by reversed-phase HPLC. The precise molecular mass and N-terminal sequence of each PLA2 were determined. In addition to the six previously documented PLA2 isoforms of this species, we identified ten novel isoforms. The venom gland cDNAs of individual specimens of the viper from four localities were used for PCR and subsequent cloning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 32 publications
(81 reference statements)
9
55
2
2
Order By: Relevance
“…Notably, disintegrins of T. stejnegeri showed high diversification and more than four isoforms could be identified. This is in accord with the unusually high diversity of its venom PLAs (Tsai et al, 2004). The disintegrins of T. stejnegeri and Gloydius halys are at the basal positions relative to those from other crotalid genera, and trigramin β is identical to albolabrin of T. albolabris.…”
Section: New Examples Of Venom Disintegrin Treesupporting
confidence: 60%
See 4 more Smart Citations
“…Notably, disintegrins of T. stejnegeri showed high diversification and more than four isoforms could be identified. This is in accord with the unusually high diversity of its venom PLAs (Tsai et al, 2004). The disintegrins of T. stejnegeri and Gloydius halys are at the basal positions relative to those from other crotalid genera, and trigramin β is identical to albolabrin of T. albolabris.…”
Section: New Examples Of Venom Disintegrin Treesupporting
confidence: 60%
“…However, the genetic relationships may also be complicated by intra-species variations, possibly resulting from prey-ecology (Daltry et al, 1997), geographic separation, ontology (Warrell, 1997), or other factors. Indeed, we found that the three Taiwanese viperid species, D. r. siamensis (Tsai et al, 1996), P. mucrosquamatus venoms (Tsai et al, 2001), and T. stejnegeri (Tsai et al, 2004), show considerable intra-species variations in their venom PLA isoforms, mainly due to differential expression of each isoforms and geographic separation of the snakes. Usually, more PLA sequences can be deduced from cloning the venom gland cDNAs than are predicted from venom purification because not all of the mRNA are translated into venom proteins (Chijiwa et al, 2000).…”
Section: B Venom Protein Evolutionmentioning
confidence: 99%
See 3 more Smart Citations